Prevalence and characterization of azole-resistant Aspergillus fumigatus in patients with cystic fibrosis: a prospective multicentre study in Germany. (19th April 2018) - Seufert, R; Sedlacek, L; Kahl, B; Hogardt, M; Hamprecht, A; Haase, G; Gunzer, F; Haas, A; Grauling-Halama, S; MacKenzie, C R; Essig, A; Stehling, F; et al.
Abstract: Objectives: Aspergillus fumigatus is the most prevalent filamentous fungus in the respiratory tract of patients with cystic fibrosis (CF). The aim of this prospective multicentre study was to investigate the prevalence of azole-resistant A. fumigatus (ARAF) in respiratory secretions from CF patients across Germany and to characterize ARAF isolates by phenotypic and molecular methods. Methods: Twelve tertiary care centres from Germany participated in the study. In total, 2888 A. fumigatus isolates from 961 CF patients were screened for ARAF by using azole-containing agar plates. Antifungal susceptibility testing of isolates was performed by broth microdilution according to EUCAST guidelines. Analysis of mutations mediating resistance was performed using PCR and sequencing of the cyp51A gene. Furthermore, genotyping by microsatellite PCR was performed. Results: Of a total of 2888 A. fumigatus isolates, 101 isolates from 51 CF patients were found to be azole resistant (prevalence per patient 5.3%). The Essen centre had the highest prevalence (9.1%) followed by Munich (7.8%), Münster (6.0%) and Hannover (5.2%). Most ARAF isolates ( n  =   89) carried the TR34 /L98H mutation followed by eight G54E/R, one TR46 /Y121F/T289A and one F219S mutation. In two isolates no mutation was found. Genotyping results showed no major clustering. Forty-five percent of CF patients with ARAF had previously received azole therapy. Conclusions: This is the first multicentre study analysing the prevalence of ARAF isolates in German CF patients. Because of a resistance rate of up to 9%, susceptibility testing of A. fumigatus isolates from CF patients receiving antifungal treatment should be part of standard diagnostic work-up.